Identity leadership and cohesion in elite sport: The mediating role of intra-team communication - Schei, G. S.; Høigaard, R.; Erikstad, M. K.; Ivarsson, A.; Haugen, T. (Heliyon, 2023)
One perspective on leadership that has recently gained increased attention in sport is identity leadership; however, research on elite sport teams is still in its infancy. Thus, the main purpose of this research is to investigate identity leadership in elite team sports in relation to task cohesion, and subsequently to explore the mediating role of the intra-team communication dimensions of acceptance and distinctiveness. A cross-sectional design was employed and 441 elite athletes from division 1 and division 2 in handball and ice hockey participated in the present study. Structural equation modeling was used to assess relationships between identity leadership and task cohesion, and the mediating role of acceptance and distinctiveness. Results revealed that identity leadership positively predicted task cohesion, and that this relationship was mediated by intra-team communication acceptance. In conclusion, findings in the present study expand our understanding of performance-related benefits of identity leadership in elite sport.